LOCAL HERITAGE (WARISAN BUDAYA) DAN PENGAJARAN BAHASA INGGRIS - Fadhillah Wiandari; Cut Intan Meutia (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2020)
This research was conducted to get an overview of local heritage in teaching English in the classroom. The teaching of foreign languages is one of the factors that can affect the neglect of existing local heritage. The teacher understands the concept of cultural heritage or local wisdom. This concept is believed to be important to be applied in language teaching and learning. This is because the teaching materials presented in the English textbook contain language content that is oriented towards general knowledge and cross-cultural knowledge. This study used a qualitative method where the data sampling techniques were carried out by purposive and snowball sampling. In this study, it was found that linking external knowledge and existing knowledge in students' daily lives was considered important to enable students to express themselves in a foreign language. However, teachers are constrained by the existing curriculum targets so that the teaching of local wisdom is solely in the textbooks.